The Impact of Orbital and Clock Errors on Positioning from LEO Constellations and Proposed Orbital Solutions - El-Mowafy, Ahmed; Wang, Kan; Li, Yan; Allahvirdi-Zadeh, Amir (2023)
Two approaches are discussed for the estimation and prediction of the orbits of low earth orbit (LEO) satellites that can be used for navigation. The first approach relays on using a ground monitoring network of stations. The procedures to generate the LEO orbital products in this approach are proposed at two accuracy levels to facilitate different positioning applications. The first type targets producing orbits at meter-level accuracy, defined here as LEO-specific broadcast ephemeris. The second type of products would produce orbits with an accuracy of cm as polynomial corrections to the first type of orbits. Real and simulated LEO satellite data is used for testing, mimicking LEO satellites that can be used for positioning. For the first type of products, it was found that orbital prediction errors play the dominant role in the total error budget, especially in cases of mid and long-term prediction. For the second type of products, the predicted orbits within a short period of up to 60 s generate errors at a few cm, and fitting the corrections with a quadratic polynomial reduced the fitting range errors to the cm level compared to the case of applying a linear polynomial. This level of accuracy can fulfill the requirement for precise point position ing (PPP). The second approach is computing the orbits in real time applying the kinematic or reduced-dynamic mode, where the orbits are computed in the PPP mode using GNSS observations collected onboard LEO satellites and the GNSS orbits and clock products are received through inter-satellite links such as the free-access SouthPAN service in Australia, Galileo HAS, or Beidou (BDS-3, PPP-B2b service). The limitations of this approach and preliminary results are given. Furthermore, the LEO satellite clocks determined together with the orbits in the reduced-dynamic LEO satellite orbit process in near-real-time are also analysed. Finally, the impact of possible orbital and clock errors in the range of decimetres to several meters of LEO satellites on positioning performance is analysed.